Identity politics: A view from the South - Kessi, Shose (PINS-Psychology in Society, 2015)
Ispas, Alexa (2013) Psychology and politics: A social identity perspective. London & New York: Psychology Press. ISBN 978-0-415-67770-7 hbk. Pages xi +129.